PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA MATA PELAJARAN IPAS MATERI KENAMPAKAN ALAM DAN BUATAN DI KELAS III SDN 189/II SARI MULYA - Anggrayni, Melissa; Margaretta Fitriani; Filahanasari, Eka (Information Technology Education Department, 2025)
This research is motivated by the limited availability of learning media, which has impacted student learning outcomes. In addition, many studens reported difficulties in underdtanding the subject matter. The aim of this study is to develop a diorama-based learning media for the IPAS subject on the topic of natural and artifical landscapes for grade III studen at SDN 189/II Sari Mulya that is valid, practical, and effective. The research method used is Research and Development (R&D), applying the ADDIE development model, which consits of five stages: Analyze, Design, Development, Implementation, and Evaluation. The diorama learning media was validated by five experts, resulting in the following scores: material aspect 93%, media aspect 92%, language aspect 94,28%, teachung module aspect 90,91%, and test item aspect 80%. The teacher’s response questionnaire, assessed by the grade homeroom teacher, received an average score of 84,77%. The effectiveness analysis indicated an average score of 81,25%. These findings suggest that the diorama learning media is valid,practical, and effective for improving student understanding in the studied subject matter.